The Influence of diabetes, hypertension, and hyperlipidemia on the onset of age-related macular degeneration in North China: the Kailuan Eye Study - Zhang, Yong Peng; Wang, Ya Xing; Zhou, Jin Qiong; Wang, Qian; Yan, Yan Ni; Yang, Xuan; Yang, Jing Yan; Zhou, Wen Jia; Wang, Ping; Shen, Chang; Yang, Ming; Luan, Ya Nan; et al. (Biomedical and environmental sciences, 2022)
Objective: To analyze the prevalence of dry and wet age-related macular degeneration (AMD) in patients with diabetes, hypertension and hyperlipidemia, and to analyze the risk factors for AMD. Methods: A population-based cross-sectional epidemiologic study was conducted involving 14,440 individuals. We assessed the prevalence of dry and wet AMD in diabetic and non-diabetic subjects and analyzed the risk factors for AMD. Results: The prevalence of wet AMD in diabetic and non-diabetic patients was 0.3% and 0.5%, respectively, and the prevalence of dry AMD was 17% and 16.4%, respectively. The prevalence of wet AMD in healthy, hypertensive, hyperlipidemic, and hypertensive/hyperlipidemic populations was 0.5%, 0.3%, 0.2%, and 0.7%, respectively. The prevalence of dry AMD in healthy, hypertensive, hyperlipidemic, and hypertensive/hyperlipidemic populations was 16.6%, 16.2%, 15.2%, and 17.2%, respectively. Age, sex, body mass index, and use of hypoglycemic drugs or lowering blood pressure drugs were corrected in the risk factor analysis of AMD. Diabetes, diabetes/hypertension, diabetes/hyperlipidemia, and diabetes/hypertension/hyperlipidemia were analyzed. None of the factors analyzed in the current study increased the risk for the onset of AMD. Conclusion: There was no significant difference in the prevalence of wet and dry AMD among diabetic and non-diabetic subjects. Similarly, there was no significant difference in the prevalence of wet and dry AMD among subjects with hypertension and hyperlipidemia. Diabetes co-existing with hypertension and hyperlipidemia were not shown to be risk factors for the onset of dry AMD.
Gesehen am 08.01.2024